The promotion effect of surface negative electrostatic field on the photogenerated charge separation of BiVO4 and its contribution to the enhanced PEC water oxidation. Issue 14 (12th January 2015) - Xie, Mingzheng; Bian, Ji; Humayun, Muhammad; Qu, Yang; Feng, Yujie; Jing, Liqiang
Abstract : The surface-carried negative charge of BiVO4 is favorable for the charge separation, leading to obviously enhanced visible-light-activity for PEC water oxidation. Abstract : The increased surface-carried negative charge of BiVO4 after phosphate modification prolongs the photogenerated charge carrier lifetime and improves the separation by inducing the holes to transfer to the surface, leading to the obvious enhancement of visible light activities for PEC water oxidation.